Biopolymers for erosion mitigation of soils observed by erosion function apparatus (EFA) - Kwon, Yeong Man; Lee, Minhyeong; Chang, Ilhan; Cho, Gye Chun (Geotechnical Special Publication, 2023)
Erosion causes severe damage to the structural integrity of infrastructure; hence, the erosion resistance of soils is one of the most crucial design requirements for the construction of water-nearby facilities. This research suggests using biopolymers, organically oriented polymers, to reduce the surface erosion of soils caused by flowing water due to their potential to improve the hydraulic and mechanical properties of soils. Using the erosion function apparatus (EFA), which replicates a laminar flow velocity of 0-5 m/s, we determined the resistance of biopolymer-Treated soils to flowing water, with embedded P-wave reflection sensors recording the eroded height to flow durations. The experimental results revealed that biopolymers significantly affected erosion control by enhancing particle contact, decreasing permeability, and filling pore spaces. In addition, biopolymer treatment significantly improved the critical shear stress and decreased the erodibility coefficient of soils. This research established a significant basis for suggesting biopolymers as stabilizers for river and seabed soil.
Keywords: Erosion function apparatus; Erosion mitigation; Erosion resistance; Flow duration; Flowing waters; Oriented polymers; P waves; Surface erosion; Treated soils; Wave reflections